2016
DOI: 10.4103/0253-7176.178774
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographically Measured Change in Thyroid Status in Lithium Treated Adult Patients with Mood Disorder

Abstract: Background:Lithium, which is frequently used in the treatment of mood disorder, can lead to various types of thyroid dysfunctions. Although clinical examination and biochemical assessment are fundamental to any thyroid work-up of lithium-treated patients, assessment findings vary widely depending on the investigator. Ultrasonographic measurement of thyroid volume has, therefore, been performed in lithium treatment populations and found to be a sensitive tool.Aim:We aimed to determine and compare thyroid gland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…On the other hand, Ozsoy, Mavili, Aydin, Turan, and Esel () found lower fT4 in the long‐term lithium‐treated patients and decreased fT3 in lithium‐naïve subjects after lithium treatment. Alam, Sinha, and Nizamie () in patients treated with lithium found higher concentrations of both total T4 and total T3. The increase of fT4 found in our long‐term lithium‐treated patients can also be seen as a compensatory phenomenon to lithium inhibition of thyroid function.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, Ozsoy, Mavili, Aydin, Turan, and Esel () found lower fT4 in the long‐term lithium‐treated patients and decreased fT3 in lithium‐naïve subjects after lithium treatment. Alam, Sinha, and Nizamie () in patients treated with lithium found higher concentrations of both total T4 and total T3. The increase of fT4 found in our long‐term lithium‐treated patients can also be seen as a compensatory phenomenon to lithium inhibition of thyroid function.…”
Section: Discussionmentioning
confidence: 89%
“…were it was found that lithium treatment is associated with increased individual mean thyroid lobe volume and overall mean thyroid volumes. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%